Peace and Hope in Dark Times - Fiala, Andrew.,; Heydari Fard, Sahar, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2023., 2023)
The papers collected here apply the insights of the philosophy of peace to contemporary issues and the larger problem of what it means to have hope and to work for peace in dark times. The authors included in this volume respond to contemporary challenges posed by the Trump Era and the COVID-19 crisis. This represents a novel application and exploration of concepts and ideas found in the philosophy of peace and nonviolence. The authors elucidate the philosophy of peace and general approaches to building peace while applying these ideas to current crises. .